POST-LISTING STOCK RETURNS AND INDUSTRY EFFECT - Niemikorpi, Olli (My University, 2006)
This study, with an evidence of 79 Finnish IPOs during 1987–2002, investigates whether the industry has impact on the behavior of stock returns after initial public offerings. In particular, it is studied whether the underpricing and the underperformance associated with IPOs exist in the Finnish stock market and whether the industry affects these phenomena. The performance is analyzed with abnormal returns which are determined by using four benchmarks. The results clearly show that Finnish IPOs are underpriced on average. Despite the method, the t-test being utilized verifies that the initial average abnormal return is statistically significant. Moreover, the results suggest that the IPOs underperform all the benchmarks in the long-run. However, the deepness of the underperformance is dependent on the underlying benchmark. The analysis indicates that the industry has a clear impact on both these anomalous phenomena. The measure of underpricing (i.e. initial abnormal return) varies from industry to another. Industrial firms are the best initial performers whereas materials sector produces the poorest initial returns. Instead, consumer discretionary & staples industry generates the best long-run returns whereas high-tech sectors are the poorest performers in the 36-month period following IPO. In addition, the Fama-French model being utilized exhibits that the whole underperformance in Finnish stock market may probably be explained with blow-outs of bubbles and different figures in market capitalizations and book-to-market values. When using the FF model, only the high-tech sectors statistically underperform. This finding suggests that the whole underperformance in Finland may be caused by anomalies related to different market values and book-to-market figures, and crashes that followed prevailing booms.
Keywords: initial public offerings; underpricing; underperformance; industry effect; abnormal returns; CAPM; Fama-French three factor model; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|